okay your slope is 6
so plug int he x's and why's
y = mx +b
2 = 6(-7) + b
2 = -42 + b
44 = b
y = 6x + 44
2006-11-02 09:27:08
·
answer #1
·
answered by abbs 2
·
0⤊
0⤋
Use the point-slope formula.
m = slope.
Our slope is 6 as given.
Our point is (-7, 2).
Plug that into y - y1 = m (x - x1)
y - 2 = 6(x -(-7))
y - 2 = 6 (x + 7)
Next:
Multiply each term inside the parentheses on the right side of the equation by the outside number 6.
We now have this:
y - 2 = 6x + 42
Add 2 to BOTH side of the equation.
You get this:
y = 6x + 44
Final answer: y = 6x + 44
2006-11-02 09:32:47
·
answer #2
·
answered by kum-Bucket69 2
·
0⤊
0⤋
You are given a point and the slope.
Use the point-slope formula.
m = slope.
Our slope is 6 as given.
Our point is (-7, 2).
Plug that into y - y1 = m (x - x1)
LOOK:
y - 2 = 6(x -(-7))
y - 2 = 6 (x + 7)
Next:
Multiply each term inside the parentheses on the right side of the equation by the outside number 6.
We now have this:
y - 2 = 6x + 42
See it?
Next: Add 2 to BOTH side of the equation.
We get this:
y = 6x + 44
Final answer: y = 6x + 44
Guido
2006-11-02 09:29:23
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
First realize the the standard equation of a line is:
y = mx + b
Next, realize you already have 3 of the 4 variables.
For (-7,2) x = -7 and y = 2 For Slope = 6, m = 6, all we have to do is solve for b
2 = 6(-7) + b
2 = -42 + b
44 = b
Now, to get the equation of the line, only enter in m and b and do not enter in x and y into the equation of a line.
So you will get the following:
y=6x+44
I hope this helps.
2006-11-02 10:43:22
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
There's a couple of ways to do this. I will use the form
Y-y=m(X-x)
Y-2=6(X- -7)
Y-2=6(X+7)
Y-2=6X+42
6X+42=Y-2
6X=Y-44
6X-Y=-44
2006-11-02 09:28:40
·
answer #5
·
answered by mom 7
·
0⤊
0⤋
First you write it in point-slope form:
y-2=6(x+7)
Now you convert that equation into standard form:
y-2=6x+42
y-6x=44
6x-y=-44
2006-11-02 09:28:56
·
answer #6
·
answered by Pascal 7
·
0⤊
0⤋
y = mx + b where m = slope and b = y intercept
2 = -42 + b
b = 44
y = 6x + 44
2006-11-02 09:27:10
·
answer #7
·
answered by disposable_hero_too 6
·
0⤊
0⤋
Okay, put in y=mx+b form, 2=(6*-7)+b, and just solve for b!
Then just put in y=6x+b!
2006-11-02 09:32:47
·
answer #8
·
answered by yljacktt 5
·
0⤊
0⤋
y-6=2(7+X)
Y-6=14+2X
Y=8+2x
I think thats it. Its been awhile since my algebra days.
2006-11-02 09:28:02
·
answer #9
·
answered by Me 2
·
0⤊
0⤋
(x - y^5)^3 = x^3 - 3x^2y^5 + 3xy^10 - y^15
2016-05-23 21:07:31
·
answer #10
·
answered by Heather 3
·
0⤊
0⤋